A Comparison of Think Pair Share and Group Investigation: Which Cooperative Learning Model Is More Effective in Biology Education? - Sigit Wibowo; Mohd Syuja (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to compare students’ Biology learning outcomes taught using the cooperative learning methods of Group Investigation and Think Pair Share, in order to identify which method leads to higher cognitive achievement in junior high school Biology learning. Methodology: This study employed a quasi-experimental design using a two-group pretest–posttest model. The research instruments included a 25-item objective test, interview guidelines, observation sheets, and an item analysis tool (ANATES). Data were collected through tests, interviews, and observations, and subsequently analyzed using tests of normality and homogeneity, N-gain analysis, and an independent samples t-test. Main Findings: The results indicate that there was no significant difference in pretest scores between the Group Investigation and Think Pair Share groups. Posttest and N-gain analyses revealed that the Think Pair Share method produced significantly higher learning outcomes than the Group Investigation method. Students in the Think Pair Share group achieved higher mean scores, demonstrated better conceptual mastery, and showed more substantial learning gains. Interview results also indicated that students were more confident, active, and focused when learning through the Think Pair Share method. Novelty/Originality of this study: This study provides a direct comparison between Group Investigation and Think Pair Share in Biology learning, an empirical investigation that has rarely been conducted. The findings contribute to the existing body of knowledge by demonstrating that Think Pair Share offers more structured interaction, better focus, and more evenly distributed participation, resulting in more effective learning compared to Group Investigation.